Living to Die and Dying to Live: The Survival Strategy behind Leaf Senescence. Issue 2 (14th August 2015) - Schippers, Jos H.M.; Schmidt, Romy; Wagstaff, Carol; Jing, Hai-Chun
Abstract : Leaf senescence is a highly dynamic process that has a major impact on crop production and quality. Abstract: Senescence represents the final developmental act of the leaf, during which the leaf cell is dismantled in a coordinated manner to remobilize nutrients and to secure reproductive success. The process of senescence provides the plant with phenotypic plasticity to help it adapt to adverse environmental conditions. Here, we provide a comprehensive overview of the factors and mechanisms that control the onset of senescence. We explain how the competence to senesce is established during leaf development, as depicted by the senescence window model. We also discuss the mechanisms by which phytohormones and environmental stresses control senescence as well as the impact of source-sink relationships on plant yield and stress tolerance. In addition, we discuss the role of senescence as a strategy for stress adaptation and how crop production and food quality could benefit from engineering or breeding crops with altered onset of senescence.